Functional geometry of the left ventricle in patients after orthotopic heart transplantation in the early postoperative period - T. V. Chumarnaya; Yu. S. Alueva; V. V. Kochmasheva; N. F. Klimusheva; A. I. Iofin; A. N. Bykov; O. E. Solov'eva (Трансплантология (Москва))
The functional geometry of the left ventricle (LV) of heart was investigated in patients after orthotopic heart transplantation without any signs of rejection. Typical features of LV functional geometry in heart transplant recipients with uncomplicated postoperative period were indentified as compared to patients without heart disease. The authors have put forward the hypothesis about a diagnostic value of LV functional geometry parameters for a non-invasive diagnosis of graft dysfunction that would facilitate an optimum correction of treatment tactics.